RANCANG BANGUN ALAT PEMOTONG BAHAN KERUPUK UBI KAYU - Firda Herlina; Ahmad Rizani (INFO-TEKNIK, 2013)
Cassava is one of several main provisions substitutes in Indonesia. It is known to be the third consumed provisions after rice and corn. The spreading of cassava plant is in all over Provinces of Indonesia. In the regency of Hulu Sungai Selatan in the Province of South Kalimantan cassava is processed to become cassava chips and thereby supports the local economic development. Unfortunately there is a lack of technology for the efficient cassava slicing machine, since the used tools are still very simple. The purposes of this research are to design and to build an efficient cassava slicing machine and also recognizing the influence of the pulley size to the slicing speed and to the sliced cassava.The preparation to invent the cassava slicing machine consists of designing and selection of its components, such as motor, axis, pulley, anvil and other supporting equipments. After the designing process the assembling of the slicing machine is executed. Right after the assembling process the performance of the slicing machine is tested by changing the rotation of slicing disc axis constantly in order to gain great quantities of qualified sliced cassavas with less waste.The result of this research and the analyzing process shows that the performance of the designed slicing machine can be optimal by using 8 inches pulley. The slicing of one stem produces 861 sliced cassavas, 645 of them are qualified and 217 are broken, in average time of 35,67 seconds. By slicing two stems at the same time produces 1.413 sliced cassavas, consist of 857 qualified and 556 broken sliced cassavas, in the average time of 45,67 seconds. The comparison for the invented slicing machine is the simple slicing machine, which is used in South Kalimantan nowadays. The simple machine slices 546 sliced cassavas from one stem, 461 of them are qualified and 85 sliced cassavas are broken, in the time of 2 minutes. The comparison shows that the new invented machine is more efficient than the used old one.  Moreover the invented cassava slicing machine has the advantages of high slicing speed, clean sliced cassava and high safety.